Rural tourism destination competitiveness: A study on Annah Rais Longhouse Homestay, Sarawak - Chin, Chee-Hua; Lo, May-Chiun; Peter, Songan; Vikneswaran, Nair (Elsevier Ltd., 2014)
Tourism industry is known as one of the largest economic sectors in most of the countries and highly contributes to the economic growth in Malaysia. Contemporary, the sustainability of tourism destination become crucial and highly contributes to the competitiveness of a rural tourism destination. Nonetheless, the high competitive environment in this industry forces tourism players to provide better services to their visitors in order to stay competitive. Hence, multiple components of environmental construct, namely, environmental conservation, environmental education, cultural heritage attractions, tourism infrastructure, and natural resources play crucial roles in attracting tourists to visit and gain sustainability for rural tourism destination. Local communities’ attitudes toward tourism development highly influence the success and failure of tourism development at the destinations. The purpose of this paper is to examine the impact of multi-environmental components towards development of tourism destination competitiveness from local communities’ perspective. A total of 80 local communities from Annah Rais Longhouse Homestay, Sarawak voluntarily took part in this study. To assess the developed model, SmartPLS 2.0 (M3) is applied based on path modeling and then bootstrapping. Interestingly, the findings from this study revealed that both cultural heritage attractions and natural resources found to have positive impact towards development of destination competitiveness from local communities’ perspective. Implications of these findings are discussed further.